Reproductive Injustice, Eugenics, and Commercial Surrogacy (International Journal of Innovative Research in Engineering & Management, 2021)
While maintaining worldwide racial reproduction hierarchy,  India's commercial surrogacy industry actually creates people and  human connections. The forceful enemy of natalism of the post pilgrim state repeats the more extensive worldwide populace  control plan, which outlines the worldwide South's high  fruitfulness rates as a "worldwide risk" that should be controlled  no matter what, yet it is at chances with the neoliberal basic of  unhindered worldwide ripeness the travel industry. Substitutes  (belly mothers) upset male centric talks by recovering control of  their bodies and giving their ripe bodies something to do. They  ultimately stick to worldwide neo-eugenic objectives to diminish  the richness of lower class ladies in the worldwide South by  controlling their own propagation through decisions about  ripeness, sanitization, and fetus removal to (re)produce posterity  of higher classes and advantaged nations. Surrogates artistically  create familial connections with the infant and the intended  mother across class, caste, religion, race, and country,  undermining dominant genetic and patriarchal underpinnings of  kinship while essentially reifying systemic inequalities.
Keywords: Commercial Surrogacy; Fertility; Globalization; Reproductive; Surrogacy